Survival and growth rates of sutchi catfish juveniles, pangasianodon hypophthalmus under different light wavelengths and intensities - Yusoff, Nor Amira; Sallehudin, Firdaus; Mukai, Yukinori (2015)
The sutchi catfish, Pangasianodon hypophthalmus is a popular fish species in aquaculture industry. However, sutchi catfish shows high mortality during larval and juvenile stages. Thus, present study investigated the effect of different light wavelengths and light intensities on the growth and survival rates of sutchi catfish juveniles. 69 days old juveniles were reared under five light wavelengths (white, blue, green, yellow and red) with three light intensities (1.40x10-3, 1.40x10-2, and 1.40x100µmoles/m²/s) in triplicates for 11 days. The present study showed the tendency of higher survival and growth rates under blue light wavelength with 1.40x10-3µmoles/m²/s.